To act or to react? The role of responsiveness in corporate social performance disclosure in preventing plastic pollution in the travel and tourism sector. (26th May 2022) - Fait, Monica; Meissner, Dirk; Gregori, Gian Luca; Monge, Filippo; Cillo, Valentina
Abstract: A corporate social performance model is dependent on strategies involving the processes of social responsiveness. From this perspective, this article observes that the voluntary disclosure of corporate social performances (CSP‐D) is a proactive behavior based on "responsiveness" because it corresponds to the ability to reduce the gap between disclosed content and the perception of the content by stakeholders. The study examines the voluntary disclosure actions undertaken through social media by 60 T&T companies to communicate to their stakeholders how they contribute to reducing environmental negative externalities, plastic pollution in particular. Then, a co‐word analysis is carried out, adopting social network maps to highlight and compare the cognitive paths that characterize disclosure and reaction. The findings suggest that when the cognitive pathways of stakeholders tend to converge towards the behavior disclosed by companies, their expectations are met and this enhances CSP‐D effectiveness. Finally, social media are suitable for generating this alignment, reducing the legitimacy gap and building a good reputation.